2015
DOI: 10.7860/jcdr/2015/13442.6619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential of CFC (Calcium hydroxide Flagyl Ciprofloxacin) for the Rapid Disinfection of Resilon and Gutta-Percha

Abstract: A 5.25% NaOCl and Biopure MTAD required less chair side time to disinfect all the samples effectively when compared with 2% CHX and CFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
2
0
4
Order By: Relevance
“…dificultando o processo de obturação dos canais radiculares, evidenciando a presença de cristais de cloro na superfície dos cones descontaminados. A presença de cristais cuboidais e estruturas arredondadas provavelmente são produtos da lise parcial de alguns componentes do cone (PANG et al, 2007;NABESHIMA et al, 2011;SUBHA et al, 2013;AKTEMUR TURKER et al, 2015;HAMZA et al, 2015). Os cones de gutapercha que foram descontaminados com hipoclorito de sódio 5,25% e foram lavados com água destilada ou álcool não apresentaram cristais de cloreto, isso indica que a lavagem após o uso de agentes químicos é necessária para que não prejudiquem a estrutura do cone e causem defeitos na obturação dos canais radiculares (PRADO et al, 2011a;TOPUZ et al, 2011).…”
Section: Ao Comparar Limas E Cones Das Marcasunclassified
See 2 more Smart Citations
“…dificultando o processo de obturação dos canais radiculares, evidenciando a presença de cristais de cloro na superfície dos cones descontaminados. A presença de cristais cuboidais e estruturas arredondadas provavelmente são produtos da lise parcial de alguns componentes do cone (PANG et al, 2007;NABESHIMA et al, 2011;SUBHA et al, 2013;AKTEMUR TURKER et al, 2015;HAMZA et al, 2015). Os cones de gutapercha que foram descontaminados com hipoclorito de sódio 5,25% e foram lavados com água destilada ou álcool não apresentaram cristais de cloreto, isso indica que a lavagem após o uso de agentes químicos é necessária para que não prejudiquem a estrutura do cone e causem defeitos na obturação dos canais radiculares (PRADO et al, 2011a;TOPUZ et al, 2011).…”
Section: Ao Comparar Limas E Cones Das Marcasunclassified
“…A presença e a persistência de microrganismos no canal radicular é a principal causa de falhas no tratamento endodôntico. Essa contaminação pode ser proveniente do tipo de armazenamento e manipulação, já que os cones são produzidos em condições assépticas (NABESHIMA et al, 2011;AKTEMUR TURKER et al, 2015;HAMZA et al, 2015;RAVI CHANDRA et al, 2015;FREIRE et al, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Various chemicals like ethyl alcohol, paraformaldehyde, formocresol, glutaraldehyde, polyvinylpyrrolidone iodine, quaternary ammonium compounds, and hydrogen peroxide are being commonly used as disinfectants. Recent studies have advocated the use of 1% peracetic acid and BioPure MTAD antibacterial root canal cleanser (DENTSPLY Tulsa Dental Specialties, DENTSPLY International, Inc., Johnson City, TN, USA) for disinfection of GP [ 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] advocated ciprofloxacin (CFC), metronidazole (Flagyl, G.D. Searle LCC, Divison of Pfizer Inc., New York City, NY, USA) and calcium hydroxide to kill Staphylococcus aureus ( S. aureus ), Pseudomonas aeruginosa , Enterococcus faecalis ( E. faecalis ), and Bacteroides fragilis . But it was concluded that CFC required a minimum of 5 minutes exposure for GP disinfection [ 8 ]. Chlorhexidine gluconate (0.2%, 1%, and 2%) both in liquid and gel forms were ineffective against Bacteroides subtilis ( B. subtilis ) spores even after 72 hours.…”
Section: Introductionmentioning
confidence: 99%